The Strategy of the Civil Service Police Unit in Controlling Street Vendors in Tangerang Regency, Banten Province - Abdul Muhyi; Faria Ruhana; Megandaru W. Kawuryan (Sean Institute, 2026)
The regulation of street vendors is one of the local government’s efforts to maintain public order and spatial management. However, in practice, enforcement activities often face various obstacles, including limited resources, low legal awareness among street vendors, and economic factors that encourage vendors to continue operating in prohibited areas. These conditions indicate the need for an appropriate strategy to ensure that enforcement activities can be carried out effectively and sustainably. This study aims to analyze the strategy of the Civil Service Police Unit in regulating street vendors in Tangerang Regency, Banten Province, covering strategy formulation, strategy implementation, strategy evaluation, strategy effectiveness, and improvement efforts through SWOT analysis. This study employed a qualitative research method with a descriptive approach. Data collection techniques included interviews, observation, and documentation. Research informants consisted of personnel from the Civil Service Police Unit of Tangerang Regency, street vendors, and community members. Data analysis was conducted through data reduction, data presentation, and conclusion drawing. The results indicate that the strategy for regulating street vendors has been implemented through stages of formulation, implementation, and evaluation. During implementation, the approaches applied included preemptive measures through socialization, preventive measures through supervision and patrols, and repressive measures through enforcement actions in accordance with procedures. However, the effectiveness of the strategy has not been fully optimal, as some street vendors returned to the same locations after enforcement activities. The main inhibiting factors include limited personnel, inadequate facilities and infrastructure, low legal awareness among vendors, limited relocation areas, and resistance from vendors. Based on the SWOT analysis, improvement strategies should focus on strengthening inter-agency coordination, increasing resource capacity, enhancing supervision, and implementing more persuasive and sustainable approaches. Therefore, the strategy implemented by the Civil Service Police Unit of Tangerang Regency still requires improvement so that enforcement activities are not merely oriented toward law enforcement but also accommodate social and economic aspects of society.